The Impact of Semi-Adjustable Articulators with Facebow Transfer on the Clinical Efficacy of Complete Dentures - Mustafa Esmaio,; Amna Aburweis,; Fatima Al-Faqeeh,; Hanadi Mosbah,; Muftah Abdelaaziz,; Osama Kafage, (AlQalam Journal of Medical and Applied Sciences, 2025)
The incorporation of semi-adjustable articulators with facebows when producing complete dentures is one of the best innovations in dental technology. Loss of teeth is not uncommon in the elderly population and presents quite significantly with functional, esthetic, and psychological impacts. Complete dentures are the most practical means for replacing missing teeth, restoring oral function, and improving overall quality of life. Despite the best manufacturing procedures, it will always present difficulties to attain comfort and exactness. As such, sophisticated instruments like the semi-adjustable articulator and facebow are needed to raise the functional performance as well as clinical accuracy. This research aims to assess the effect of the utilization of a semi-adjustable articulator with facebow on the functionality of complete dentures, focusing on enhancing occlusal support and increasing the level of the wearer's comfort. The survey consisted of 40 respondents (22 women and 18 men), evenly divided between the technicians and the dentists, and with direct responses from the patients. The findings indicated good chewing stability in 93.34% of the patients with reduced difficulty in speech. Amongst the professionals, the semi-adjustable articulator was used regularly by 57.5% and the facebow by 42.5%. In addition, there were improved impression tray positioning accuracies with the instruments for 85% respondents and verification for increasing tooth arrangement for 80% respondents. In addition, there were reduced occlusal adjustments for 85% respondents and reduced TMJ pain-associated complaints for 82.5% respondents. The integration of semi-adjustable articulators with facebows significantly improves the precision and stability of complete dentures, aligning with previous studies that highlight their role in enhancing occlusal accuracy and reducing patient discomfort. Thereby enhancing patient comfort.